Immigration Participation in Social Assistance Programs - Regina T. Riphahn (Institute for the Study of Labor (IZA), 1998)
The share of foreigners in the German social assistance program exceeds their population share and continues to grow. This study tests whether higher foreigner welfare dependence is due to foreign-native differences in behavior as opposed to exogenous characteristics. The determinants of welfare dependence are analyzed using data from the German Socioeconomic Panel (1984-1996). Panel attrition and welfare dependence processes are modelled jointly. The difference in aggregate welfare dependence appears to be due to characteristics, where the household head?s labor market status and single parent status are central, with significant differences in the response rates of German and foreign households to given characteristics. The controls for attrition have strong effects on the estimation and simulation results.
Keywords: J61; I38; 330; immigration; social assistance; welfare dependence; Internationale Wanderung; Ausländer; Sozialhilfeempfänger; Schätzung; Familiensoziologie; Humankapital; Deutschland